Voices of children : experiences with violence - Cabral, Christie (Ministry of Labour, Human Services and Social Security GeorgetownGY, 2005)
Addresses the impact of different forms of violence on the lives of children in Guyana. Indicates the actions taken by the Ministry of Labour, Human Services and Social Security, in partnership with civil society organisations and the United Nations Children's Fund, to ensure that all children in Guyana can grow up without violence.